Planning for the future of derelict farm premises: From abandonment to regeneration?. (March 2021) - Klusáček, Petr; Navrátil, Josef; Martinát, Stanislav; Krejčí, Tomáš; Golubchikov, Oleg; Pícha, Kamil; Škrabal, Jaroslav; Osman, Robert
Highlights: Two-thirds of derelict farm premises experience long-term abandonment. Planning for derelict farm premises is different from planning for current agricultural use. Two-thirds of derelict farm premises are planned to be re-used in agriculture. Housing is another important re-use option for such premises. Actual regeneration generally follows the requirements of territorial zoning plans. Abstract: Re-using and regenerating derelict and abandoned areas constitutes an important element in sustainable land use policy and planning. This paper explores the phenomenon of derelict farm premises in South Bohemia, the Czech Republic. It analyses the origin and extent of this phenomenon as well as land use targets applied to such sites by planning documents. A large number of derelict farm premises have emerged on former collectivized lands. According to local territorial zoning plans, agricultural use prevails as the reuse designation for these sites. However, they are still significantly less frequently planned to be used in agriculture than areas currently in active agricultural use and are more frequently planned to be converted into housing, public buildings, or industrial activities. Overall, strategies for the planned utilization of derelict premises are found to be contingent on temporal and spatial factors. While many long-term derelict premises are planned to be converted into non-agricultural use, newly emerged ones are more likely to retain the agricultural designation. In terms of spatial diversity, rural municipalities of the inner peripheries emphasize housing development rather than industrial activity. Further, by analysing successful regeneration projects accomplished for abandoned premises since 2004, it is found that they generally adhere to the requirements of territorial zoning plans.